STUDY OF KAPAH CLAM (Meretrix sp.) MANAGEMENT IN AMAL BEACH ZONE TARAKAN CITY, EAST KALIMANTAN - Wiharyanto, Dhimas (Jurnal Harpodon Borneo, 2012)
Amal beach is the side of Tarakan Island and it has high biodiversity. One of fauna found which associated with the mangroves is kapah clam (Meretrix sp.). That has economic value so that faced high exploited along season. Considering that condition study of kapah clam management was very importance. This study were studied from September until October 2009 until December 2010 . This study use primer and secondary data’s include ecology and capture information. SWOT analysis used to take for certain management strategies. Kapah clam (Meretrix sp) collected at intertidal area with survey method and stratified systematic sampling. In each location divided based on zonations area i.e. upper, middle, lower and investigated by using belt transects with frame 1x10 m2 divided in 10 subplot. The distribution, and mean density of the shell were difference at each station. Management strategies priority for kapah clam at Amal beach are : monitoring of Kapah clam source at Amal Lama Beach, selection size in capture, management time for capture, Determine of protecting area and maintaining with restocking. Keywords : Amal Lama beach, Meretrix, Strategic management